2012
DOI: 10.1017/s0022149x12000430
|View full text |Cite
|
Sign up to set email alerts
|

Cystic echinococcosis in slaughtered domestic ruminants from Tunisia

Abstract: A total of 10,818 domestic ruminants (3913 cattle, 2722 sheep, 3779 goats, 404 dromedaries) slaughtered in various abattoirs in Tunisia between 2003 and 2010 were examined for the presence of Echinococcus granulosus hydatid cysts. The prevalence of cystic echinococcosis (CE) was 16.42% in sheep, 8.56% in cattle, 5.94% in dromedaries and 2.88% in goats. CE prevalence increased with age according to an asymptotic model and there was evidence of variation in infection pressure depending on the region of Tunisia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
37
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 40 publications
9
37
5
Order By: Relevance
“…In Tunisia, previous studies investigating the zoonotic parasites of small mammals were focused mainly on those that cause diseases, such as leishmaniasis and echinococcosis, known to impact humans (Ghawar et al, 2011;Toumi at al., 2012;Lahmar et al, 2013). Moreover, most of the available studies on helminths in this area are relatively old, are mainly related to taxonomy or life cycle studies (Bernard, 1969(Bernard, , 1987Bernard and Ben Rachid, 1969;Quentin, 1978), or have focused on a single host species and/or single parasite species (FichetCalvet et al, 2003;Faleh et al, 2012).…”
mentioning
confidence: 97%
“…In Tunisia, previous studies investigating the zoonotic parasites of small mammals were focused mainly on those that cause diseases, such as leishmaniasis and echinococcosis, known to impact humans (Ghawar et al, 2011;Toumi at al., 2012;Lahmar et al, 2013). Moreover, most of the available studies on helminths in this area are relatively old, are mainly related to taxonomy or life cycle studies (Bernard, 1969(Bernard, , 1987Bernard and Ben Rachid, 1969;Quentin, 1978), or have focused on a single host species and/or single parasite species (FichetCalvet et al, 2003;Faleh et al, 2012).…”
mentioning
confidence: 97%
“…In Tunisia, Echinococcus infections are widespread in dogs (prevalence above 20%) and domestic ruminants, with prevalence levels of 16.4; 8.56; 2.8; 5.9; 8.4% reported in sheep, cattle, goats, camels and equines, respectively [ Fig. 12 and Table S11 and S12 of the Supplementary Material] (Lahmar et al, 2013. The rural domestic cycle is primarily maintained by sheep and cattle intermediate hosts in north and central regions and by camels in the south.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Furthermore, like many rodent species, acting as reservoirs and spreaders of zoonoses, is a major concern, and the study of parasites of wide geographic areas has medical and veterinary importance to prevent transmission of diseases to human and domestic animals. Many studies have reported the important role of these two Meriones species in cutaneous leishmaniasis (Ben Ismail et al 1987;Rassi et al 2006;Ghawar et al 2011;Derbali et al 2012;Lahmar et al 2013;Mirzaei et al 2013;Aoun & Bouratbine 2014). However, little is known about the diversity of their internal parasites, and more information on the diversity and distribution of helminths is necessary.…”
Section: Introductionmentioning
confidence: 99%